Інформаційні права і свободи людини та їх судовий захист у конституційних нормах Сербії - Музичук, К.; Muzychuk, К. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У статті йдеться про відображення інформаційних прав і свобод людини, їх судовий захист та особливості судочинства в Конституції Сербії відповідно до вимог демократичного суспільства. Встановлено загальний алгоритм оцінки судом правильності здійснення обмежень інформаційних прав і свобод людини, відповідно до принципів демократії. Здійснено порівняльно-правове дослідження відповідних норм Конституцій Сербії та України, виявлено резерви посилення захисту інформаційних прав людини в вітчизняному праві. The article deals with the representation of informational rights and liberties of a humans, their judicial defence and the peculiarities of the Constitution of Serbia according to the demands of democratic society. The common algoritm of the correct way of execution of restrictions of information rights and liberties according to the principles of democracy was established. The given algorithm identifies the constitutional demands urith the Convention of defence of rights of with the practice of European court of rights of a man. The basis of judicial defence of information rights in Serbia is the principle of democracy: the fundamental rights of a man and liberties can only be extended.
Informational Rights and Liberties of a Humans, Their Judicial Defence in the Constitutional Regulations of Serbia
Keywords: інформаційні права і свободи людини; судовий захист; Конституція Сербії; information rights and liberties; judicial defence; the Constitution of Serbia; democracy